Simultaneous Analysis of Noise and Vibration of Machines in Vibroacoustic Diagnostics - DĄBROWSKI, Zbigniew; DZIURDŹ, Jacek (Archives of Acoustics, 2016)
The article is a continuation of the authors' elaboration (Dąbrowski, Dziurdź, 2016). The aim of this continuation is to prove that a proposed way of modelling and using the coherent analysis to filter nonlinear disturbances is a useful technique in vibroacoustic diagnostics. The thesis was proved by solving the task of diagnosing the damage of the gear of the car gearbox on the basis of the measurement of mechanical vibrations and the noise in the engine chamber.